Application of an improved version of the erosion potential method in alpine areas - Milanesi, Luca; Pilotti, Marco; Clerici, Alberto; Gavrilovic, Zoran (Italian journal of engineering geology and environment, 2015)
The assessment of erosive processes is of great importance in environmental engineering, resource management and land planning. In this paper the empirical approach known as Erosion Potential Method (EPM) was improved to simplify the identification of the involved parameters. In addition, EPM suitability for alpine watersheds, where the average yearly temperature may be below 0°C, was discussed. The advantages of distributed approaches rather than lumped methodologies were tested. EPM was then implemented in a distributed form for a set of 31 catchments located in Alta Valtellina (Northern Italy) in order to capture the spatial variability of the parameters and the intensity of the erosion processes. The results obtained for these catchments were positively compared to long-term sedimentation data from three reservoirs and from a turbidimetric station.